Effect of Cognitive Dual Task Training versus Motor Dual Task Training on Balance in Post Stroke Patients - Sukala, N.; V., Rajalaxmi (INTI International University, 2021)
OBJECTIVE: This study aims to compare the effects of cognitive dual task training and motor dual task training on balance in post stroke patients. INTRODUCTION : Stroke is a disease caused by lack of blood supply to the brain following ischemia or haemorrhage. The reduced motility following stroke results in a body imbalance that appears as asymmetric posture, proprioception disorder and abnormal muscle tone that lead to the degeneration of balancing ability. Dual tasks training is a training in which two or more tasks are performed at the same time continuously. The motor dual tasks requires performance of a motor task and a postural control task at the same time and cognition dual tasks requires performance of a cognition task and postural control task simultaneously. MATERIALS AND METHODS: Thirty participants fulfilling the inclusion criteria were selected and divided into 2 groups with 15 participants each. Participants in CDTT or MDTT practiced the cognitive and motor dual tasks respectively while standing on wobble board. The intervention was for 45 minute / session, 5 days/week for 4 weeks Participants were tested before and after the intervention for balance function under cognitive and motor dual task conditions using berg balance scale, stroop test and standing balance test. RESULTS: Mean values of Group A and Group B on berg balance scale, were (49.47) and (47.40) respectively. Mean values of Group A and Group B on standing balance test were (30.07) and (28.80), and the mean values of Group A and Group B on stroop test were (16.73) and (11.47). On comparing pre test and post test values within Group A and Group B on berg balance scale, standing balance test and stroop test shows highly significant difference in mean values at p ≤ 0.001. CONCLUSION: This study concluded that cognitive dual task training is more effective in improving balance in acute stroke patients with balance impairment, when compared to motor dual task training.